Tracing memories and meanings of festival landscapes during the COVID-19 pandemic. (August 2022) - Katczynski, Amelie; Stratford, Elaine; Marsh, Pauline
Abstract: COVID-19 has deeply affected mass gatherings and travel and, in the process, has transformed festivals, festival landscapes, and people's sense of place in relation to such events. In this article we argue that it is important to better understand how people's memories of festival landscapes are affected by these larger shifts. We worked from the premise that information-rich cases could provide some initial insights in this respect. To that end, we interviewed seven individuals who are regular and longstanding in their engagement with festivals in one place, lutruwita/Tasmania, the island state of Australia. Key findings suggest that pandemic experiences mediate the range of meanings participants give to festival landscapes and their interpretations of such landscapes can be described as attachments and detachments, encounters, and reorientations. We conclude by proposing that participants' efforts to draw on memories, reflect on emotional geographies, and recast autobiographies help them adjust to crises, rethink their ways of moving to and from festival sites, and reframe their sense of place in relation to significant cultural events. Such insights have application beyond both the island state and the participants involved. Highlights: The experience of the COVID-19 pandemic affects how people remember and give meanings to festival landscapes. Experiences of immobility during the pandemic gave extra potency to physical engagements with festival landscapes. A sense of social connectedness and dynamics of physical encounters at festivals were missed during lockdown. COVID-19 prompted people to reassess and reconfigure their relationships with festivals and their landscapes. Memories and biographies are important factors in people's sociospatial adjustments to crises, such as the pandemic.